Pengembangan Media Pembelajran Game Edukasi Berbasis Wordwall dan Educaplay dalam Meningkatkan Minat Belajar Siswa Kelas IX di MTs Hidayatul Muhajirin (International Forum of Researchers and Lecturers, 2024)
This study aims to develop and design Media based on Educational Games Wordwall and Educaplay on fiqh muamalah material class IX MTs Hidayatul Muhajirin. In order to increase the learning interest of ninth grade students at MTs Hidayatul Muhajirin. The method used is development research (R&D) with the ADDIE model, which includes five stages: analysis, design, development, implementation, and evaluation. The research subjects consisted of 26 ninth grade students of MTs Hidayatul Muhajirin. Data was collected through Google Form after the use of the media, as well as feedback regarding students' learning experience. The results showed that the use of this educational game significantly increased students' interest in learning. The average score of students' interest in learning before the use of the media was 60, which increased to 92 after implementation. In addition, students showed higher enthusiasm for learning and actively participated in class activities. This study concludes that educational game-based learning media can be an effective alternative in increasing students' interest in learning. It is hoped that the results of this study can make a positive contribution to the learning process at MTs Hidayatul Muhajirin and become a reference for further learning media development.